Massive macroglossia, amyloidosis and myeloma. Issue 755 (September 1988) - Jacobs, P.; Sellars, S.; King, H. S.
Abstract : A 74 year old man with light-chain myeloma developed amyloidosis with macroglossia after 10 years of therapy with alkylating agents. Over a 2-year period his tongue enlarged to persistently protrude from his mouth, inhibit his speech, interfere with normal swallowing and eventually threaten his airway. As a life-saving procedure the tumorous anterior two-thirds of the tongue was resected, with excellent primary healing. Within two weeks the patient's speech became comprehensible and his ability to eat returned to normal. Although rare in amyloidosis, massive macroglossia may occur and surgical correction is easily achieved.